GAYA BAHASA PERBANDINGAN DALAM NOVEL SI ANAK PINTAR KARYA TERE LIYE - Anjani, Fitri; Syam, Christanto; Wartiningsih, Agus (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2020)
AbstractThis research was focused on the main comparative style of language contained in the novel The Child Smart by Tere Liye. The problem in this research is,what language styles are contained in the novel of Si Anak Pintar by Tere Liye, what are the comparative language styles, the meaning of comparative language styles, and the implementation of this research in Indonesian learning. The method in this research is descriptive with a qualitative form. The approach used is a statistical approach. The data collection technique used is documentary study technique. Based on the results of data analysis of comparative language styles contained in the novel Si Anak Pintar by Tere Liye, there are 69 units, which include 19 similes, 19 personifications, 5 hyperbole, 6 metaphors, 6 pre-toto synekdok, 14 associations , perifrase 4 pieces, and defemism 1 piece. The most dominant comparative language style contained in the novel Si Anak Pintar by Tere Liye is a simile and personification style of 19 items. The analysis was carried out by determining the comparative style of language contained in the Si Anak Pintar novel in the form of words, phrases, clauses, and sentences.Â Keywords: Comparative Language Style, The Smart Child